Estimated glucose disposal rate demographics and clinical characteristics of young adults with type 1 diabetes mellitus: A cross-sectional pilot study. (September 2020) - Nishtala, Revathi; Kietsiriroje, Noppadol; Karam, Mohammad; Ajjan, Ramzi A; Pearson, Sam
Background: Estimated glucose disposal rate (eGDR) is a practical measure of Insulin Resistance (IR) which can be easily incorporated into clinical practice. We profiled eGDR in younger adults with type 1 diabetes mellitus (T1DM) by their demographic and clinical characteristics. Methods: In this single centre study, medical records of TIDM were assessed and eGDR tertiles correlated with demographic and clinical variables. Results: Of 175 T1DM individuals, 108 (61.7%) were males. Mean age (±SD) was 22.0 ± 1.6 years and median time from diagnosis 11.0 years (range 1–23). Individuals were predominantly Caucasian (81.7%), with 27.4% being overweight (BMI: 25–30 kg/m 2 ) and 13.7% obese (BMI > 30 kg/m 2 ). Mean total cholesterol (TC) levels were significantly lower in high and middle eGDR tertiles (4.4 ± 1 and 4.3 ± 0.8 mmol/l, respectively) compared with low eGDR tertile (4.8 ± 1, p < 0.05 for both). Triglyceride (TG) levels showed a similar trend at 1.1 ± 0.5 and 1.1 ± 0.5 mmol/l for high and middle eGDR tertile compared to low eGDR tertile (1.5 ± 1 mmol/l, p < 0.05 for both). Renal function was similar across eGDR tertiles and no difference in retinopathy was detected. Conclusion: TC and TG are altered in individuals with T1DM and low eGDR, suggesting that this subgroup requires optimal lipid management to ameliorate their vascular risk.